2012
DOI: 10.1167/iovs.12-9872
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Administration into the Suprachoroidal Space Using a Microneedle for Drug Delivery to the Posterior Segment of the Eye

Abstract: Injection into the suprachoroidal space using a microneedle offers a simple and minimally invasive way to target the delivery of drugs to the choroid and retina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
228
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 205 publications
(233 citation statements)
references
References 20 publications
4
228
0
1
Order By: Relevance
“…Hollow microneedles were used to deliver insulin in subjects with type 1 diabetes at 1 mm depth. [ 41 ] Microneedles have also been used to deliver drugs into other biological tissues such as the eye [ 42 ] and the nasal mucosa. [ 43 ] They can also be incorporated onto vascular stents (Figure 8 b).…”
Section: Microneedlesmentioning
confidence: 99%
“…Hollow microneedles were used to deliver insulin in subjects with type 1 diabetes at 1 mm depth. [ 41 ] Microneedles have also been used to deliver drugs into other biological tissues such as the eye [ 42 ] and the nasal mucosa. [ 43 ] They can also be incorporated onto vascular stents (Figure 8 b).…”
Section: Microneedlesmentioning
confidence: 99%
“…To overcome some of these barriers, newer approaches for delivering the drug closer to the target side have emerged. Patel et al [75] developed hollow microneedles that are able to deliver the drug solution directly into the suprachoroidal space located between the sclera and the choroid and adjacent to the target site for the treatment of most retinal diseases. Although studies have shown promising results for delivering large molecular weight antibodies into this space, [75] it remains to be seen whether this delivery route could also be explored for ocular gene therapy.…”
Section: Ocular Gene Therapymentioning
confidence: 99%
“…Patel et al [75] developed hollow microneedles that are able to deliver the drug solution directly into the suprachoroidal space located between the sclera and the choroid and adjacent to the target site for the treatment of most retinal diseases. Although studies have shown promising results for delivering large molecular weight antibodies into this space, [75] it remains to be seen whether this delivery route could also be explored for ocular gene therapy. ABCA4, photoreceptor-specific ABC transporter gene; AMD, age-related macular degeneration; BDNF, brain derived neurotrophic factor; BIRC4, human baculoviral IAP repeat containing protein 4 (caspase inhibitor); CB1, cannabinoid receptor 1; CEP290, centrosome protein with a mass of 290 kDa; CHM/CHML: human gene that encodes for Rab proteins geranylgeranyltransferase component A 2; CNGB3 and CNGA3, cone-specific cyclic nucleotide gated channel beta and alpha; CNTF, ciliary neurotrophic factor.…”
Section: Ocular Gene Therapymentioning
confidence: 99%
“…Suprachoroidal cannulation and drug delivery were also reported to be damaging to the outer retina, including photoreceptors, in the primate eye model [10]. The most recent studies from Tyagi et al and Patel et al were encouraging and a good safety profile was depicted using a 34 gauge needle or a microneedle for the suprachoroidal injection [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the amount of Avastin reaching the retina from suprachoroidal delivery was limited and cleared more quickly compared with intravitreal delivery [13]. In contrast, sodium fluorescein seems to behave differently [11,12]. Though suprachoroidal delivery may be different from subtenon and intravitreal routes, a sustained drug delivery formulation is equally important for all these ocular delivery routes.…”
Section: Introductionmentioning
confidence: 99%